Imobilização de fosfatos em microesferas poliméricas contendo biochar: preparação, caracterização e liberação lenta em sistemas aquosos - Domingues, Murilo Teles [UNESP] (2015)
The world population is growing and can reach 9 billion people by the year 2050. This will result in greater production of food to meet this demand. In agriculture, for example, will be used larger amounts of conventional fertilizers to increase agricultural production, increasing the leaching of nutrients, such as phosphorus, for water resources, polluting them. Thus, as an alternative to replace conventional fertilizers, this study aimed to prepare, characterize and evaluate, in an aqueous medium, the phosphorus slow release of polymeric alginate microspheres containing biochar (pyrolyzed organic matter). To achieve that, were produced five kinds of biochars from sugarcane bagasse to heat it to temperatures of 300, 400, 500, 600 and 700 °C (B300, B400, B500, B600 and B700, respectively). The increasing in pyrolysis temperature rises the pH of the formed material due to an increased formation of carbonates and reduction of functional groups with acidic characteristics. The yield was inversely proportional to the temperature increasing, since, when raise the temperature rises the decomposition of organic matter, thereby obtaining a lower yield. The B300 and B400 showed still have the remnants of hemicellulose in its composition, which would prove that the pyrolysis up to 400 °C, and the conditions here adopted, were not sufficient to complete decomposition of this structure in the sugarcane bagasse. The increase in pyrolysis temperature increased aromaticity and decreased hydrophilicity, or its affinity for water. The B700 had higher ash content that could serve as nutrients for plants, however, the B300 and B400 have the highest content of organic matter, which can be more easily degraded by microorganisms. It was observed the presence of pores in biochars since 300 °C pyrolysis temperature, but it is noted that from 500 °C biochar showed different structural variants, resulting in different pore complex. In the phosphorus release ...